Cleaning Pakistan's Air : Policy Options to Address the Cost of Outdoor Air Pollution - Sanchez-Triana, Ernesto; Enriquez, Santiago; Afzal, Javaid; Nakagawa, Akiko; Khan, Asif Shuja (Washington, DC: World Bank, 2014)
Pakistan's urban air pollution is among the most severe in the world and it engenders significant damages to human health and the economy. Air pollution, inadequate water supply, sanitation, and hygiene are the top environmental priority problems in Pakistan. Industrialization and urbanization, in conjunction with motorization, can result in further deterioration of urban air quality. This book examines policy options to strengthen the Pakistan clean air program (PCAP) to better address the cost imposed by outdoor air pollution upon Pakistan's economy and populace. The approach provided in this book recommends that the federal and provincial environmental protection agencies (EPAs) take on a limited number of high return, essential, and feasible interventions drawn largely from the PCAP. The objective of this book is to examine policy options to control outdoor air pollution in Pakistan. The findings of the analysis aim at assisting the Government of Pakistan (GoP) in the design and implementation of reforms to improve the effectiveness and efficiency of Pakistan's ambient air quality institutions. The overarching theme of this book is that prioritizing interventions is essential to address the cost of outdoor air pollution, given current resource limitations. The book also includes a review of secondary sources, focusing on recent analysis of the effects of different air pollutants on human health, as well as lessons learned from ongoing regional and international efforts to improve ambient air quality. This book has seven chapters. Chapter one gives overview. Chapter two identifies major trends in ambient air pollution, including concentration levels of main pollutants and the identification of principal sources. Chapter three examines the evolution of Pakistan's air quality management (AQM) framework over the period 1993 to 2013. Chapter four examines options to control air pollution from mobile sources, the main contributors of several air pollutants, including noxious fine particulate matter (PM) and its precursors. Chapter five addresses measures to tackle pollution from industrial sources. Chapter six identifies synergies of interventions for air pollution control and climate change mitigation. Chapter seven summarizes the main conclusions of the book.